Effect of 10 freshwater microalgae on in vitro methane mitigation and rumen fermentation - Li, Yang; Bagnoud-Velásquez, Mariluz; Zhang, Yixin; Wang, Kai; Punčochářová, Lenka; Kunz, Carmen; Dubois, Sebastian; Peng, Rong; Brahier, Alexandra Baumeyer; Wahl, Fabian; Niu, Mutian (Journal of dairy science, 2025)
Agriculture is at the pivot point between anthroposphere, biosphere, and atmosphere. Innovative solutions are needed to reduce agricultural emissions and improve sustainability. Microalgae animal feed could be such a solution. This study aimed to evaluate the effects of 10 freshwater microalgae: Auxenochlorella protothecoides, Chlamydomonas pulvinate, Chlorella luteoviridis, Chlorella variabilis, Euglena mutabilis, Parachlorella kessleri, Stichococcus bacillaris, Tetradesmus acuminatus, Tetradesmus obliquus, and Tetraselmis gracilis, on ruminal methane (CH4) production, nutrient digestibility, and rumen fermentation using the in vitro Hohenheim gas test. The microalgae were cultured in a carbon dioxide (CO2) incubator at 2% CO2, at the optimal conditions for each strain. The highest producers were P. kessleri and T. obliquus, with a biomass concentration of 0.69 and 0.73 g/L·d, respectively. Their PUFA contents ranged from 33.2% to 69.1% of total fatty acids. Microalgae were tested at a 15% replacement in a control basal diet of 40.0% DM grass silage, 40.0% maize silage, 15% hay, and 5% concentrate. Data were analyzed using a mixed model in R. Ruminal CH4 production was reduced by 15.4%, 17.4%, and 16.4% in diets containing A. protothecoides, C. luteoviridis, and P. kessleri, respectively, compared with the control diet. Similarly, these diets reduced in vitro organic matter digestibility by 3.5%, 5.2%, and 5.4%, respectively. However, only A. protothecoides reduced CH4/CO2 ratio by 3.5% compared with the control diet. Propionate molar proportion was decreased by 2.4, 3.0, 2.5, and 2.5 percentage points for diets containing Ch. pulvinate, E. mutabilis, P. kessleri, and T. obliquus, respectively. Marginal effects of dietary variables were analyzed using the generalized additive model framework, revealing a negative relationship between dietary PUFA, sulfur content, and CH4 production, and a negative relationship between dietary PUFA and CH4/CO2 ratio. Incorporating high-PUFA microalgae in ruminant diets shows potential for reducing enteric CH4 emissions, warranting further investigation.
Keywords: mikrořasy; methane mitigation; ruminant; siláž; Methane; bachor; methan; Animal Feed; zvířata; Animals; Microalgae; Fermentation; sladká voda; Rumen; Silage; trávení; Digestion; dieta; krmivo pro zvířata; PUFA; Fresh Water; rumen fermentation; fermentace; skot; Diet; Cattle; microalgae